2019
DOI: 10.1038/s41531-019-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria function associated genes contribute to Parkinson’s Disease risk and later age at onset

Abstract: Mitochondrial dysfunction has been implicated in the etiology of monogenic Parkinson’s disease (PD). Yet the role that mitochondrial processes play in the most common form of the disease; sporadic PD, is yet to be fully established. Here, we comprehensively assessed the role of mitochondrial function-associated genes in sporadic PD by leveraging improvements in the scale and analysis of PD GWAS data with recent advances in our understanding of the genetics of mitochondrial disease. We calculated a mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 59 publications
4
95
0
Order By: Relevance
“…Interestingly it was shown that the exclusion of all SNVs located in genomic regions with known PD susceptibility loci did not reduce predictive power of the PD polygenic risk scores (Reynolds et al 2019). Focusing on variants in mitochondrial genes a polygenic risk of small effect variants was shown to contribute to disease risk and AAO in PD (Billingsley et al 2019). These findings suggest that mainly common variants with small effect sizes (not reaching genome-wide significance in GWAS) are contributing to disease risk.…”
Section: Polygenic Risk Scoresmentioning
confidence: 99%
“…Interestingly it was shown that the exclusion of all SNVs located in genomic regions with known PD susceptibility loci did not reduce predictive power of the PD polygenic risk scores (Reynolds et al 2019). Focusing on variants in mitochondrial genes a polygenic risk of small effect variants was shown to contribute to disease risk and AAO in PD (Billingsley et al 2019). These findings suggest that mainly common variants with small effect sizes (not reaching genome-wide significance in GWAS) are contributing to disease risk.…”
Section: Polygenic Risk Scoresmentioning
confidence: 99%
“…Furthermore, recruiting patients from the QPN Participant Registry provides an opportunity to access a large number of patients who are of French-Canadian ancestry, which was critical for the recent identification of a founder mutation in the GBA gene in French-Canadian patients with PD or RBD [25]. Genome-wide association study (GWAS) data from QPN patients have also been used for recent largescale genetic analyses of mitochondria-related genes and GWAS of AAO in PD [47,48]. The GWAS data are currently being used to accurately determine the ancestry of all participants, and these data will be made available for the users of QPN data.…”
Section: Recent Studies and Trials Facilitated By The Quebec Parkinsomentioning
confidence: 99%
“…Comparably, we report a highly significant down-regulation of mitochondria, exosome, and brain expressed miRNAs over time in PD. In particular, mitochondria dysfunction seems to play a major role in the disease, although it is still unclear whether it's part of the cause or a consequence of the disease 43 . Shamir et al 44 described affected gene interactions networks in iPD to be associated with oxidation, ubiquitination and other hallmarks of PD, an effect that is mirrored by the dys-regulated miRNAs revealed in our analysis of the PPMI cohort.…”
Section: Discussionmentioning
confidence: 99%